Disinfection of Viruses 2022
DOI: 10.5772/intechopen.104520
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Persistence of SARS-CoV-2 and Disinfection of Work Surfaces in View of Pandemic Outbreak of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is primarily a respiratory illness, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The pandemic outbreak of SARS-CoV-2 across the world has been responsible for high morbidity and mortality, which emphasizes the role of the environment on virus persistence and propagation to the human population. Since environmental factors may play important roles in viral outbreaks, and the severity of the resulting diseases, it is essential to take into account th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…So, it can be concluded that transmission of SARS-CoV-2 can be through direct contact with droplets and aerosol particles, as well as contact with the surface of objects. 20 There are five stages of the virus life cycle in cells: attachment, penetration, biosynthesis, maturation, and release. In the process (attachment), the virus will bind to the host cell's receptor, after which the virus will enter (penetrate) by endocytosis and membrane fusion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So, it can be concluded that transmission of SARS-CoV-2 can be through direct contact with droplets and aerosol particles, as well as contact with the surface of objects. 20 There are five stages of the virus life cycle in cells: attachment, penetration, biosynthesis, maturation, and release. In the process (attachment), the virus will bind to the host cell's receptor, after which the virus will enter (penetrate) by endocytosis and membrane fusion.…”
Section: Literature Reviewmentioning
confidence: 99%